Influencing Factors on Nurses' Motivation to Pursue Bachelor’s Degree. A Study in a Class B Hospital in West Jakarta - Situmorang, Indah Mestika; Hilmy, Mohamad Reza Hilmy; Anindita, Rina (International Journal of Nursing and Health Services (IJNHS), 2025)
Background: Hospital X, a state-owned enterprise, aims to increase the ratio of nurses with a Bachelor of Nursing degree to 30:70, but the current ratio is reversed, necessitating an increase in this number. Objective: This study aims to evaluate the influence of social support, and hospital organizational support mediated by self-concept factors on the motivation of nurses to continue formal education. Methods: Quantitative research and a questionnaire, with a 4-point Likert Scale were distributed. There were 489 respondents and 320 respondents met the inclusion criteria. The data was analyzed using three-box method and SEM-PLS. Results: Social support and self-concept independently influence the motivation of the nurses to pursue a Bachelor’s degree. However, organization support does not affect the motivation of nurses. The role of self-concept as a mediator to motivate nurses is significantly positive. Social support and organization support; each have a positive influence on self-concept.  Conclusion: Hospital X must calculate the needs of qualified nurses with a Bachelor of Nursing degree and follow it with talent scouting, mentoring, and leadership training programs to improve nurses’ self-concept. Providing scholarships or tuition assistance can increase the perception of organization support, which further increases commitment and loyalty of the nurses. Recommendation: The equalization Bachelor of Nursing degree program must be improved to utilize the potential of nurses who have already obtained the degree independently. Further study to explore the type of organization support and other motivational factors is also needed